ANALISIS HUKUM TENTANG WEWENANG NOTARIS DALAM PEMBUATAN AKTA IKRAR WAKAF - Ari Latif Pratama (Universitas Sriwijaya, 2015)
Abstract : Government Regulation No. 42 year 2006 was on the implementation of Law No.41 year 2004 on waqf / endownment. According to the regulation, waqif could make the pledge deed of waqf (AIW) both before the notary and the Office of Religious Affair. The problem was whether all the notaries had authorization to make the the pledge deed of waqf (AIW) based on the regulation for pledge deed officer of waqf (PPAIW). This study was a normative study which analyzed a legal enforceability and was conducted by examining law materials, such as research on the principles of law, rule of law, and legal norm. This study used two approaches: statue approach and historical approach. The result showed that the authority of notary in making the pledge deed of waqf (AIW) was authorized in Goverment Regulation No. 42 year 2006 article 37. This authority did not contradict to the authority of notary as regulated in Government Regulation No. 2 year 2014 article 15 concerning to the amandment of law no. 30 year 2004 on notary. However, not all notaries could be appointed as deed officer of waqf (PPAIW). There were three basic requirements for becoming PPAIW: 1) a moslem, 2) trustworthy, and 3) having certificateof competency in waqf issued by the Ministry of Religious Affair. It was associated with the waqf/endowment itself as a religious charity. Furthermore, if there is a dispute about it, the Ministry of Religious Affair who always handle the case of moslems will solve it. The role of notary as PPAIW is as a party who gives legal certainty, collects authentic information about waqf, and provides services to the community. It was suggested this information should be socialized and a notary should be appointed as PPAIW. Howeever, cooperation among the Ministry of Religious Affair, Indonesian Waqf Board, National Land Agency, Islamic Financial Institution, Professional Association of Notary, and the Land Deed Officer is needed.